2000
DOI: 10.1385/bter:73:3:259
|View full text |Cite
|
Sign up to set email alerts
|

Iron Distribution in Different Tissues in Rats Following Exercise

Abstract: Iron plays an essential role in blood oxygen transport and in muscle physiology. No conclusive data exist in the literature concerning its tissue distribution and behavior following exercise and training. The aim of the present work was to analyze the Fe content in different tissues following a single session of swimming to exhaustion and after swimming training in rats in order to more extensively describe the changes of Fe distribution provoked by exercise. Animals were divided into four groups (n=10): contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Taking into account that at the end of exercise the rats in the three different exercise groups were all at varying developmental stages and had their different exercise duration, we propose that the effects of regular exercise, along with a high dietary iron content, on liver iron stores and duodenal iron absorption depend on individual body development/ growth in growing rats. This may explain the conflicting results on liver iron levels in exercised rats in previous studies [13][14][15][16], in which the rats displayed different levels of development. However, it should be noted that our study did not separate the effects of the duration of exercise training from the timing of exercise training within the rat's life cycle.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Taking into account that at the end of exercise the rats in the three different exercise groups were all at varying developmental stages and had their different exercise duration, we propose that the effects of regular exercise, along with a high dietary iron content, on liver iron stores and duodenal iron absorption depend on individual body development/ growth in growing rats. This may explain the conflicting results on liver iron levels in exercised rats in previous studies [13][14][15][16], in which the rats displayed different levels of development. However, it should be noted that our study did not separate the effects of the duration of exercise training from the timing of exercise training within the rat's life cycle.…”
Section: Discussionmentioning
confidence: 86%
“…Two human studies, using radio-iron labeling methods, showed that exercise decreased or increased the feces iron content in athletes with prelatent ID or low serum ferritin, respectively [23,24], while a third report [25], using a stable isotope iron technique, showed a decrease in iron absorption during exercise rather than a resting period in juvenile athletes. In both rat studies [12,16], the fecal radio-iron activity increased and decreased, respectively. Therefore, our study was designed to determine if regular exercise affects iron absorption and the mechanism for these effects, by examining 59 Fe transfer kinetics in the isolated duodenal segments of rats.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations